Pengaruh Literasi Digital dan Lingkungan Belajar Terhadap Hasil Belajar Mata Pelajaran Ekonomi di SMA Negeri 2 Singaraja - Wedayanti, Made Fanny; Santi, Ni Wayan Ayu (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the influence of digital literacy and the learning environment on student learning outcomes. The research that will be used in this study is quantitative research. Data collection is carried out by distributing questionnaires, and then the data is processed using the SPSS application. The collected data will be tested by descriptive statistical analysis, instrument tests, classical assumption tests, and hypothesis tests. The total respondents were 297 students. The results of hypothesis testing gave the following results: (1) digital literacy has a positive and significant effect on learning outcomes in economics subjects in grades X, XI and XII at SMA N 2 Singaraja, (2) the learning environment has a positive and significant effect on learning outcomes in economics subjects in grades X, XI and XII at SMA N 2 Singaraja and (3) digital literacy and the learning environment have a significant effect simultaneously on learning outcomes in subjects economics class X, XI and class XII at SMA N 2 Singaraja.